Photoionization of hydrogen atoms by coherent intense high-frequency short laser pulses: direct propagation of electron wave packets on large spatial grids - Demekhin, Philipp V.; Hochstuhl, David; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2013)
The time-dependent Schrödinger equation for the hydrogen atom and its interaction with coherent intense high-frequency short laser pulses is solved numerically exactly by propagating single-electron wave packets. Thereby, the wave function is followed in space and time for times longer than the pulse duration. Results are explicitly shown for 3 and 10 fs pulses. Particular attention is paid to identifying the effect of dynamic interference of photoelectrons emitted with the same kinetic energy at different times in the rising and falling sides of the pulse as predicted by Demekhin and Cederbaum [Phys. Rev. Lett. 108, 253001 (2012)]. In order to be able to see the dynamic interference pattern in the computed electron spectra, the photoelectron wave packet has to be propagated over long distances. Clearly, the complex absorption potentials often employed to compute the spectra of emitted particles cannot be used to detect dynamic interference. For the considered high-frequency pulses of 3 and 10 fs duration, this requires enormously large spatial grids. The photoionization and above-threshold ionization spectra presently computed are found to exhibit pronounced dynamic interference patterns. The patterns are in very good agreement with previously published results on the photoionization spectra, where available, which were computed using a completely different method, thus supporting the previously made assumption that the above-threshold ionization processes are very weak for the considered pulse intensities and high carrier frequency. The quiver motion in space and time of a free electron in strong laser pulses is also investigated numerically. Finally, a discussion is presented of how fast the atom is ionized by an intense pulse.
Gesehen am 11.12.2020